PUBLIC HEALTH ASPECTS – MISUSE AND INAPPROPRIATE USE OF ANTIBIOTICS - Miljković, Ana; Koprivica , Marko (Srpski medicinski časopis Lekarske komore, 2025)
Introduction/Aim: Since their discovery, antibiotics have represented a key defense against bacterial infections, but an increasing number of strains are developing resistance through spontaneous genetic mutations and the acquisition of resistance genes, a process further stimulated by their improper and frequent use. This literature review encompasses studies published between 2010 and 2024 and analyzes four key areas: the misuse and inappropriate application of antibiotics, the development of superbugs, the global aspects of antimicrobial resistance (AMR), and preventive strategies with an emphasis on the role of vitamins. This review aims to present evidence on antibiotic misuse, resistance development, and preventive strategies, with particular attention to the importance of vitamins in maintaining immunity and improving the functioning of healthcare systems. Methods: This literature review includes studies published from 2010 to 2024, focusing on the analysis of antibiotic misuse, the development of superbugs, the global impact of AMR, and the role of vitamins in prevention strategies. Results: The results indicate that the most common causes of inadequate therapy are self-medication, prescription without microbiological confirmation, and poor communication between physicians and patients. AMR has been recognized as one of the greatest threats to public health, with significant consequences for morbidity, mortality, and healthcare system costs. Preventive measures include education of healthcare professionals and the general population, regulation of antibiotic sales, the development of new diagnostic and therapeutic methods, and the promotion of healthy lifestyle habits. Of particular importance are vitamins with antioxidant properties (retinol, tocopherol, and L-ascorbic acid), which may reduce the need for antibiotics, especially with the contribution of vitamin D, known to stimulate the immune system. Conclusion: An integrated approach, in line with the One Health concept, is crucial for preserving the effectiveness of existing drugs and reducing the public health burden caused by AMR.